Creep fracture mechanism in welded joints of P91 steel. (1st September 2013) - Abd El-Azim, M E; El-Desoky, O E; Ruoff, H; Kauffmann, F; Roos, E
Abstract : The creep rupture strength of the welded joint of P91 steel (9Cr-1Mo-V-Nb) is limited by that of the fine grained region of its heat affected zone (HAZ). The fine grained HAZ has the lowest creep rupture strength, and the creep voids are mostly concentrated in this region in comparison with the coarse grained HAZ, the weld metal and the base metal of the welded joint. This is mainly due to the higher rate of recovery of the subgrain structure (coarsening of subgrains and recovery of dislocations within the subgrains) in the fine grained HAZ. Type IV fracture occurred in the fine grained HAZ of the cross-weld specimens after the long term creep tests at low stresses at 600 and 650°C. It occurred by the formation of creep voids. There are two types of voids. The first is the voids that form wedge type cracks at the triple points between the prior austenite grain boundaries at intermediate stresses at 600 and 650°C. The second is the voids that form round type cracks on the prior austenite grain boundaries and the subgrain boundaries at low stresses in long term creep tests at 600 and 650°C. These voids form at the interfaces between the matrix and the coarse intergranular particles of Laves, Z and Cr rich carbide phases.